Preliminary evaluation of the effectiveness of moisture removal and energy usage in pretreatment module of waste cooking oil for biodiesel production - Palanisamy K.; Idlan M.K.; Saifudin N. (Institute of Physics Publishing, 2023)
Waste Cooking Oil (WCO) is a plausible low cost biodiesel feedstock but it exhibits few unfavorable parameters for conversion into biodiesel. One of the parameter is the presence of high moisture content which will inhibit or retard catalyst during the acid esterification or base transesterification causing lower purity and yield of biodiesel. This will effect the post processing and escalate production cost making WCO a not favorable biodiesel feedstock. Therefore, it is important to have an effective moisture removal method to reduce the moisture content below 0.05%wt or 500 ppm in WCO for an efficient biodiesel production. In this work, the effectiveness of moisture removal and the energy usage of a newly develop innovative pretreatment module has been evaluated and reported. Results show that the pretreatment module is able to reduce up to 85% to effectively reduce the moisture content to below 500ppm of the initial moisture content of WCO and only consume 157 Wh/l energy compared to conventional heating that consume 386 Wh/l and only remove 67.6% moisture in 2 hours. Published under licence by IOP Publishing Ltd.